Strategi Penerjemahan Nama Diri dan Kecenderungan Ideologi dalam Versi Terjemahan Novel Animal Farm Karya George Orwell - Ina Mina Saroh (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
This paper aims to identify strategies for translating self-names (proper nouns) and ideological tendencies in translation works. The data sources used were the translated novel entitled Binatangisme (translated by Mahbub Djunaidi) as the source text and the English novel entitled Animal Farm by George Orwell as the source text. This research used the theory designed by Davies (2003) to identify translation strategies and ideological tendencies. According to Davies, there are seven translation strategies, namely preservation, addition, localization, omission, globalization, transformation and creation. The result obtained is that the translated version tends to domestication ideology. Of the 15 data analyzed, Mahbub Djunaidi's translated version has 46.67% tendencies of domestication ideology and 40% tendencies of foreignization ideology (the number is not 100% because some data using omission are considered neutral and not counted).